1991
DOI: 10.1254/jjp.57.91
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitization to Ambulation-Increasing Effect of Methamphetamine after Repeated Administration to Mice in Activity Cages of Different Sizes

Abstract: ABSTRACT-We have demonstrated that repeated administration of methampheta mine (MAP) 1 2 mg/kg, s. c. in a tilting-type round activity cage with a diameter of 20 cm (20 cm-cage) at 1 7 day intervals produces progressive enhancement of the ambulation-increasing effect (AIE), showing sensitization (reverse tolerance) in mice. However, almost no sensitization was observed when mice had been pretreated with the same doses of MAP but confined in a narrow environment repeatedly. In this ex periment, changes in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…If the slip-down is considered to be a result of increase of ambulation, the present findings agree with a previous report [3]. However, Hirabayashi et al reported that the ambulation-increasing effect of MAP was significantly enhanced on platforms with diameters greater than 15 cm [1]. This may suggest that the slipdown has a behavioral meaning different from increase of the ambulation.…”
supporting
confidence: 91%
“…If the slip-down is considered to be a result of increase of ambulation, the present findings agree with a previous report [3]. However, Hirabayashi et al reported that the ambulation-increasing effect of MAP was significantly enhanced on platforms with diameters greater than 15 cm [1]. This may suggest that the slipdown has a behavioral meaning different from increase of the ambulation.…”
supporting
confidence: 91%
“…It could be argued, for example, that the ability of SCH 23390 to block the effects of repeated quinpirole or apomorphine treatments on subsequent sensitivity to apomorphine is due to a general depression of locomotor activity rather than to a specific blockade of dopamine D1 receptors (cf Hirabayasi et al 1991). Although this explanation cannot be exclusively ruled out on the basis of the present results, there are several arguments against this view.…”
Section: Discussionmentioning
confidence: 65%
“…Figure 1(I) shows the protocol used for inducing the development and expression of locomotor sensitization with METH in male C3H/HeN (WT, MT 1 KO, MT 2 KO, MT 1 /MT 2 KO) mice during the light (ZT 5–7) and dark phases (ZT 19–21). VEH or METH pretreatments and challenge after four full days of abstinence were administered in a novel environment that is, cylindrical arenas 20 cm in diameter [25]. Locomotor activity was recorded continuously for 2 hr after treatment to assess the temporal development of sensitization by METH.…”
Section: Resultsmentioning
confidence: 99%